A large amount of slag cement activator and its preparation method
Patent Information
- Application Number
- CN202410843506.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-06-27
AI Technical Summary
[0004]但是矿渣一般采用水淬急冷方式形成,在此过程中液相来不及结晶即形成玻璃体,存在异磨性差、早期活性低的问题,一定程度上限制了其在水泥中的用量
[0023](1)本发明激发剂中,早强组份可以向低碳矿渣水泥浆体中引入大量的AlO2-、SO42-和OH-,其中的OH-可促进矿渣玻璃体溶解,AlO2-、SO42-会和体系的Ca2+发生反应,生成AFt,提高早期强度;
Smart Images

Figure BDA0004915051930000061 
Figure BDA0004915051930000071
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cement admixture technology, specifically relating to an activator for high-volume slag cement and its preparation method. Background Technology
[0002] Cement is an important component of concrete. Its production process can be summarized as "two grinding and one burning" (raw material grinding, clinker calcination, and clinker grinding). The main CO2-generating processes are coal combustion, limestone decomposition, and electricity and heat consumption. For every ton of clinker produced, approximately 0.8-1.0t of CO2 is generated.
[0003] Blast furnace slag is a molten silicate and aluminate mineral discharged during the blast furnace smelting of pig iron in the steel industry, typically accounting for 30-35% of pig iron production. The chemical composition and mineral composition of slag are similar to those of silicate cement clinker. When used as an admixture in cement production, CO2 is only generated and emitted during the electricity consumption (and in some processes, fuel combustion) of the grinding process. Replacing clinker with slag in a proportional manner can reduce CO2 emissions during the clinker production stage. If slag is used in cement production to replace clinker, carbon dioxide emissions can be significantly reduced.
[0004] However, slag is generally formed by water quenching and rapid cooling. During this process, the liquid phase does not have time to crystallize before forming a glassy body, which results in poor abrasiveness and low early activity, thus limiting its use in cement to some extent.
[0005] Currently, most activators for slag cement are used in the preparation of cement with a small amount of slag added. Their effectiveness is poor for cement with a large amount of slag added. For example, Chinese patent application CN202010050676.7 discloses a slag cement activator and its preparation method. The raw materials, calculated by mass fraction, include: polyethylene glycol 5%-10%, polyvinyl alcohol 2%-5%, polyvinylpyrrolidone 2%-8%, diethanolmonoisopropanolamine 10%-30%, and water 15%-60%. The pH range of the slag cement activator is 5-12. All raw materials are stirred at 10℃-60℃ for 20-120 min to obtain the slag cement activator.
[0006] Therefore, developing an activator for high-volume slag cement to improve the grinding efficiency of large cement is a pressing technical problem that needs to be solved. Summary of the Invention
[0007] To address the aforementioned problems, this invention provides an activator for high-volume slag cement, which can improve the grinding efficiency of high-volume slag cement and effectively enhance its compressive strength. To achieve the above objectives, this invention employs the following technical solution.
[0008] An activator for high-volume slag cement comprises the following raw materials in parts by weight: 20-50 parts of early-strength component, 2-5 parts of reinforcing component, 3-8 parts of grinding aid component, 0.1-0.5 parts of static elimination component, 0.1-1 parts of stabilizing and solubilizing component, and 30-70 parts of water.
[0009] Furthermore, the early strength component includes aluminum sulfate, sodium thiocyanate, and sodium hydroxide.
[0010] Furthermore, the weight ratio of aluminum sulfate, sodium thiocyanate, and sodium hydroxide in the early strength component is (30-60):(10-20):1.
[0011] Furthermore, the reinforcing components include sodium fluoroborate, magnesium hydroxide, and glycolic acid.
[0012] Furthermore, the weight ratio of sodium fluoroborate, magnesium hydroxide, and glycolic acid in the reinforcing component is (4-8):(2-5):1.
[0013] Furthermore, the grinding aid components include triethanolamine and sodium alkyl succinate disulfonate.
[0014] Furthermore, the weight ratio of triethanolamine to sodium alkyl succinate disulfonate in the grinding aid component is (5-10):1.
[0015] Furthermore, the static elimination component is dodecyl dimethyl tertiary amine.
[0016] Furthermore, the stabilizing and solubilizing components include urea, aluminum dihydroxyaminoacetate, and carbomer, with a weight ratio of (10-50):(2-5):1.
[0017] A method for preparing an activator for high-volume slag cement includes the following preparation steps:
[0018] (1) Add water to the reactor, start stirring, add aluminum sulfate and sodium thiocyanate to the reactor in proportion, and heat to 40℃.
[0019] Keep the temperature at -60℃ for 0.5-1h until the aluminum sulfate is completely dissolved. Then, prepare a 30% sodium hydroxide solution and add it dropwise over 0.5-1h. Continue to keep the temperature at -60℃ for 2-3h to obtain the early strength component solution.
[0020] (2) Add stabilizing and solubilizing components, grinding aid components, strengthening components and static elimination components to the early strength component solution in batches.
[0021] Stir well and cool to room temperature to obtain the activator.
[0022] Beneficial effects
[0023] (1) In the activator of the present invention, the early strength component can introduce a large amount of AlO2 into the low carbon slag cement paste. - SO4 2- and OH - OH - It can promote the dissolution of slag glass, AlO2 - SO4 2- The Ca of the system 2+ A reaction occurs, generating AFt, which increases early strength;
[0024] (2) The magnesium hydroxide crystal nuclei in the reinforcing component can lower the nucleation barrier of CSH, promote C3S hydration, fill the microstructure voids and pores formed by rapid solidification, and glycolic acid can react with Ca in the slag powder particles. 2+ Mg 2+ The reaction promotes the dissolution of ions, F - It can replace the O in the Si-O or Al-O bonds in slag glass. 2- They respectively form [SiO3F] 3- [AlO3F] 4- Reduce the number of oxygen bridges, decrease the degree of polymerization of silicon-oxygen tetrahedra, and improve the reactivity of slag powder;
[0025] (3) The grinding aid uses both triethanolamine and sodium alkyl succinate disulfonate. Their combined use provides highly efficient adsorption, not only penetrating into the cracks of the slag particles and filling the micro-cracks, making them difficult to heal on their own, but also creating a "wedge effect" on existing cracks, accelerating crack propagation and thus promoting the refinement of slag particles. It can also more effectively reduce the surface energy of the slag powder, which is beneficial for the formation and propagation of cracks in the slag particles during grinding.
[0026] (4) Add dodecyl dimethyl tertiary amine as an electrostatic elimination component. The addition of dodecyl dimethyl tertiary amine can form a conductive grid to allow static charge to move. Some of it is dissipated into the surrounding air and carried away by the air inside the mill, while some of it is neutralized with the surrounding opposite charge, thereby accelerating the dissipation of surface charge and preventing particle aggregation caused by static electricity.
[0027] (5) The addition of stabilizing and solubilizing components, including urea, aluminum dihydroxyaminoacetate, and carbomer, can form a network structure in the slag cement system, which greatly slows down the settling of solid particles and increases the stability of the system.
[0028] (6) The activator for slag cement in this invention is composed of early strength component, reinforcing component, grinding aid component, static elimination component, and stabilizing solubilizing component. The synergistic effect of each component can improve the grinding efficiency of slag cement with large dosage and effectively improve its compressive strength. After adding the activator of this invention, the 45μm decreases by 3-3.5%, the 3d compressive strength of cement mortar increases by 4.1-5.4MPa, and the 28d compressive strength increases by 5.9-8.9MPa. The grinding aid and reinforcing effects are significantly better than those of commercially available grinding aids. Detailed Implementation
[0029] The technical solution of the present invention will be further described below with reference to specific embodiments, but it is not limited thereto.
[0030] Example 1
[0031] An activator for high-volume slag cement comprises the following raw materials in parts by weight: 20 parts of early-strength component, 5 parts of reinforcing component, 3 parts of grinding aid component, 0.5 parts of static elimination component, 0.1 parts of stabilizing and solubilizing component, and 70 parts of water.
[0032] The weight ratio of aluminum sulfate, sodium thiocyanate, and sodium hydroxide in the early strength component is 30:20:1.
[0033] The weight ratio of sodium fluoroborate, magnesium hydroxide, and glycolic acid in the reinforcing component is 8:2:1.
[0034] The weight ratio of triethanolamine to sodium alkyl succinate disulfonate in the grinding aid component is 5:1.
[0035] The static eliminator component is dodecyl dimethyl tertiary amine.
[0036] The stabilizing and solubilizing components include urea, aluminum dihydroxyaminoacetate, and carbomer, in a weight ratio of 10:5:1.
[0037] A method for preparing an activator for high-volume slag cement includes the following preparation steps:
[0038] (1) Add water to the reactor, turn on the stirrer, add aluminum sulfate and sodium thiocyanate to the reactor in proportion, and heat to...
[0039] Keep the temperature at 40℃ for 1 hour until the aluminum sulfate is completely dissolved. Then, prepare a 30% sodium hydroxide solution and add it dropwise over 0.5 hours. Continue to keep the temperature at 40℃ for 3 hours to obtain the early strength component solution.
[0040] (2) Add the stabilizing and solubilizing components, grinding aid components, strengthening components and static elimination components to the early strength component solution in batches, stir evenly, and cool to room temperature to obtain the activator.
[0041] Example 2
[0042] An activator for high-volume slag cement comprises the following raw materials in parts by weight: 50 parts of early-strength component, 2 parts of reinforcing component, 8 parts of grinding aid component, 0.1 parts of static elimination component, 1 part of stabilizing and solubilizing component, and 30 parts of water.
[0043] The weight ratio of aluminum sulfate, sodium thiocyanate, and sodium hydroxide in the early strength component is 60:10:1.
[0044] The weight ratio of sodium fluoroborate, magnesium hydroxide, and glycolic acid in the reinforcing component is 4:5:1.
[0045] The weight ratio of triethanolamine to sodium alkyl succinate disulfonate in the grinding aid component is 10:1.
[0046] The static eliminator component is dodecyl dimethyl tertiary amine.
[0047] The stabilizing and solubilizing components include urea, aluminum dihydroxyaminoacetate, and carbomer, with a weight ratio of 50:2:1.
[0048] A method for preparing an activator for high-volume slag cement includes the following preparation steps:
[0049] (1) Add water to the reactor, turn on the stirring, add aluminum sulfate and sodium thiocyanate to the reactor in proportion, heat to 60℃ and keep warm for 0.5h. After the aluminum sulfate is completely dissolved, add sodium hydroxide solution with a mass concentration of 30% by dripping. The addition is completed in 1h. Continue to keep warm for 2h to obtain the early strength component solution.
[0050] (2) Add the stabilizing and solubilizing components, grinding aid components, strengthening components and static elimination components to the early strength component solution in batches, stir evenly, and cool to room temperature to obtain the activator.
[0051] Example 3
[0052] An activator for high-volume slag cement comprises the following raw materials in parts by weight: 30 parts of early-strength component, 4 parts of reinforcing component, 6 parts of grinding aid component, 0.3 parts of static elimination component, 0.5 parts of stabilizing and solubilizing component, and 54 parts of water.
[0053] The weight ratio of aluminum sulfate, sodium thiocyanate, and sodium hydroxide in the early strength component is 50:10:1.
[0054] The weight ratio of sodium fluoroborate, magnesium hydroxide, and glycolic acid in the reinforcing component is 5:3:1.
[0055] The weight ratio of triethanolamine to sodium alkyl succinate disulfonate in the grinding aid component is 8:1.
[0056] The static eliminator component is dodecyl dimethyl tertiary amine.
[0057] The stabilizing and solubilizing components include urea, aluminum dihydroxyaminoacetate, and carbomer, with a weight ratio of 20:3:1.
[0058] A method for preparing an activator for high-volume slag cement includes the following preparation steps:
[0059] (1) Add water to the reactor, turn on the stirring, add aluminum sulfate and sodium thiocyanate to the reactor in proportion, heat to 50°C and keep warm for 40 minutes. After the aluminum sulfate is completely dissolved, add sodium hydroxide solution with a mass concentration of 30% by drop. The addition is completed in 0.8 hours. Continue to keep warm for 2.5 hours to obtain the early strength component solution.
[0060] (2) Add the stabilizing and solubilizing components, grinding aid components, strengthening components and static elimination components to the early strength component solution in batches, stir evenly, and cool to room temperature to obtain the activator.
[0061] Example 4
[0062] An activator for high-volume slag cement comprises the following raw materials in parts by weight: 40 parts of early-strength component, 3 parts of reinforcing component, 5 parts of grinding aid component, 0.2 parts of static electricity eliminator component, 0.7 parts of stabilizing and solubilizing component, and 49 parts of water.
[0063] Furthermore, the weight ratio of aluminum sulfate, sodium thiocyanate, and sodium hydroxide in the early strength component is 55:15:1.
[0064] Furthermore, the weight ratio of sodium fluoroborate, magnesium hydroxide, and glycolic acid in the reinforcing component is 6:4:1.
[0065] Furthermore, the weight ratio of triethanolamine to sodium alkyl succinate disulfonate in the grinding aid component is 6:1.
[0066] Furthermore, the static elimination component is dodecyl dimethyl tertiary amine.
[0067] Furthermore, the stabilizing and solubilizing components include urea, aluminum dihydroxyaminoacetate, and carbomer, with a weight ratio of 30:4:1.
[0068] A method for preparing an activator for high-volume slag cement includes the following preparation steps:
[0069] (1) Add water to the reactor, turn on the stirrer, add aluminum sulfate and sodium thiocyanate to the reactor in proportion, and heat to...
[0070] Keep warm at 45℃ for 1 hour until the aluminum sulfate is completely dissolved. Then, prepare a 30% sodium hydroxide solution and add it dropwise over 1 hour. Continue to keep warm for 3 hours to obtain the early strength component solution.
[0071] (2) Add the stabilizing and solubilizing components, grinding aid components, strengthening components and static elimination components to the early strength component solution in batches, stir evenly, and cool to room temperature to obtain the activator.
[0072] Comparative Example 1
[0073] An activator for high-volume slag cement comprises the following raw materials in parts by weight: 30 parts of early-strength component, 4 parts of reinforcing component, 6 parts of grinding aid component, 0.5 parts of stabilizing and solubilizing component, and 54 parts of water.
[0074] The weight ratio of aluminum sulfate, sodium thiocyanate, and sodium hydroxide in the early strength component is 50:10:1.
[0075] The weight ratio of sodium fluoroborate, magnesium hydroxide, and glycolic acid in the reinforcing component is 5:3:1.
[0076] The weight ratio of triethanolamine to sodium alkyl succinate disulfonate in the grinding aid component is 8:1.
[0077] The stabilizing and solubilizing components include urea, aluminum dihydroxyaminoacetate, and carbomer, with a weight ratio of 20:3:1.
[0078] A method for preparing an activator for high-volume slag cement includes the following preparation steps:
[0079] (1) Add water to the reactor, turn on the stirring, add aluminum sulfate and sodium thiocyanate to the reactor in proportion, heat to 50°C and keep warm for 40 minutes. After the aluminum sulfate is completely dissolved, add sodium hydroxide solution with a mass concentration of 30% by drop. The addition is completed in 0.8 hours. Continue to keep warm for 2.5 hours to obtain the early strength component solution.
[0080] (2) Add the stabilizing and solubilizing components, grinding aid components and strengthening components to the early strength component solution in batches, stir evenly, and cool to room temperature to obtain the activator.
[0081] In this comparative example, except that no static elimination component is added to the raw material composition, the other raw materials and preparation methods are the same as in Example 3.
[0082] Comparative Example 2
[0083] An activator for high-volume slag cement comprises the following raw materials in parts by weight: 30 parts of early-strength component, 6 parts of grinding aid component, 0.3 parts of static electricity eliminator component, 0.5 parts of stabilizing and solubilizing component, and 54 parts of water.
[0084] In this comparative example, except that no reinforcing components are added to the raw material composition, the other raw materials and preparation methods are the same as in Example 3.
[0085] Comparative Example 3
[0086] An activator for high-volume slag cement comprises the following raw materials in parts by weight: 30 parts of early-strength component, 4 parts of reinforcing component, 6 parts of grinding aid component, 0.3 parts of static elimination component, 0.5 parts of stabilizing and solubilizing component, and 54 parts of water.
[0087] The weight ratio of aluminum sulfate, sodium thiocyanate, and sodium hydroxide in the early strength component is 50:10:1.
[0088] The weight ratio of sodium fluoroborate, magnesium hydroxide, and glycolic acid in the reinforcing component is 5:3:1.
[0089] The grinding aid component is triethanolamine.
[0090] The static eliminator component is dodecyl dimethyl tertiary amine.
[0091] The stabilizing and solubilizing components include urea, aluminum dihydroxyaminoacetate, and carbomer, with a weight ratio of 20:3:1.
[0092] A method for preparing an activator for high-volume slag cement includes the following preparation steps:
[0093] (1) Add water to the reactor, turn on the stirring, add aluminum sulfate and sodium thiocyanate to the reactor in proportion, heat to 50°C and keep warm for 40 minutes. After the aluminum sulfate is completely dissolved, add sodium hydroxide solution with a mass concentration of 30% by drop. The addition is completed in 0.8 hours. Continue to keep warm for 2.5 hours to obtain the early strength component solution.
[0094] (2) Add stabilizing and solubilizing components, grinding aid components, strengthening components and static elimination components to the early strength component solution in batches.
[0095] Stir well and cool to room temperature to obtain the activator.
[0096] In this comparative example, except that only conventional triethanolamine is used in the grinding aid component, the other raw materials and preparation methods are the same as in Example 3.
[0097] Performance testing
[0098] To further verify the effectiveness of the activator of this invention, Examples 1-4, Comparative Examples 1-3, and the commercially available grinding aid HLA-GO10 were respectively incorporated into cement at a dosage of 0.1% of the total cement weight. A blank comparative example was also included, i.e., no admixtures were added. A total of 9 experimental groups were set up, with each group repeated 5 times. The various properties were statistically analyzed and compared, and the average value of the experimental results was taken.
[0099] Cement raw material mix proportions: clinker 25wt%, slag 70wt%, gypsum 5wt%.
[0100] Experimental procedure: The moisture content of all raw materials was controlled below 1%. Raw material particles crushed to 1mm-7mm were mixed evenly and set aside. One part was used to prepare a blank sample without activator (grinding aid), and the other part was used to prepare a control sample with activator (grinding aid).
[0101] 1) Preparation of blank samples
[0102] Cement clinker, slag, and gypsum were mixed in a mass ratio of 25:70:5, and 5 kg of the mixture was prepared. This mixture was then ground in a suitable small test mill until the specific surface area reached 370 m². 2 / kg±10m 2 / kg, record grinding time T s The cement residue on a 45μm sieve was measured according to GB / T1345. Then, the strength of the ground cement was tested according to the national standard GB / T17671-2021 "Test Method for Strength of Cement Mortar", and the setting time and other properties were tested according to the national standard GB / T1346-2011.
[0103] 2) Preparation of comparative samples
[0104] Prepare two 5kg portions of cement clinker, slag, and gypsum according to the same method as the blank sample. Add the grinding aid (activator) evenly to the clinker at the recommended dosage (internal admixture). Grind to T... s The grinding time (Ttime as described in A.4.2) is used for two grinding cycles. The first-cycle sample, which contains grinding aid (activator), is discarded, and the residue on a 45μm sieve of the second-cycle sample is measured. The ground cement is then tested for strength according to the national standard GB / T17671-2021, "Test Method for Cement Mortar Strength," and its setting time and other properties are tested according to the national standard GB / T1346-2011.
[0105] The performance test results are shown in Table 1 below.
[0106] Table 1 Cement performance test results
[0107]
[0108]
[0109] As shown in Table 1, after adding the activator of this invention, the 45μm thickness decreased by 3-3.5%, the 3-day compressive strength of cement mortar increased by 4.1-5.4 MPa, and the 28-day compressive strength increased by 5.9-8.9 MPa. The grinding aid and strengthening effects were significantly better than those of commercially available grinding aids. However, changes to the key components (1-3) resulted in a decrease in all properties of the obtained cement samples.
[0110] This is because during the crushing process, cement breaks the covalent bonds within the particles, resulting in changes in electron density. This leads to the appearance of interlaced active sites for calcium and oxygen ions on both sides of the fracture surface. Without external shielding, these active sites attract each other, causing the fractured interface to tend to heal, resulting in material aggregation during grinding. The role of the electrostatic eliminator is to rapidly adsorb onto the particle surface, forming an adsorption layer to reduce surface energy and providing external ions or molecules to neutralize free charges and unsaturated valence bonds on the fracture surface, eliminating the tendency to aggregate and preventing the fractured particle surfaces from recombining. Compared to Example 3, Comparative Example 1, without the electrostatic eliminator, showed a significantly smaller reduction in particle size of 45 μm, resulting in coarser particles and a poorer grinding aid effect. Simultaneously, the coarser cement fineness affected strength development. Comparative Example 3, using conventional grinding aid components, lacked the synergistic grinding aid effect of sodium alkyl succinate disulfonate, leading to a decrease in grinding aid effect and similarly coarser particles. Comparative Example 2, lacking the reinforcing component, also showed varying degrees of overall performance degradation, with a more significant decrease in strength. It is evident that the addition of the reinforcing component, the static elimination component, and sodium alkyl succinate disulfonate in this invention is crucial for improving the performance of high-volume slag cement; the absence of any one of these components will weaken the effect.
[0111] It should be noted that the above embodiments are merely some preferred embodiments of the present invention, and not all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
Claims
1. An activator for high-volume slag cement, characterized in that, The raw materials include the following parts by weight: 20-50 parts of early strength component, 2-5 parts of reinforcing component, 3-8 parts of grinding aid component, 0.1-0.5 parts of static elimination component, 0.1-1 parts of stabilizing and solubilizing component, and 30-70 parts of water; the early strength component is aluminum sulfate, sodium thiocyanate, and sodium hydroxide, with a weight ratio of (30-60):(10-20):1; the reinforcing component is sodium fluoroborate, magnesium hydroxide, and glycolic acid, with a weight ratio of (4-8):(2-5):1; the grinding aid component is triethanolamine and sodium alkyl succinate disulfonate, with a weight ratio of (5-10):1; the static elimination component is dodecyl dimethyl tertiary amine; the stabilizing and solubilizing component includes urea, aluminum dihydroxyaminoacetate, and carbomer, with a weight ratio of (10-50):(2-5):
1.
2. A method for preparing the activator for high-volume slag cement as described in claim 1, characterized in that, The preparation steps include the following: (1) Add water to the reactor, turn on the stirring, add aluminum sulfate and sodium thiocyanate to the reactor in proportion, heat to 40℃-60℃ and keep warm for 0.5-1h. After the aluminum sulfate is completely dissolved, add sodium hydroxide solution with a mass concentration of 30% by drop. The addition is completed in 0.5-1h. Continue to keep warm for 2-3h to obtain the early strength component solution. (2) Add the stabilizing solubilizing component, grinding aid component, strengthening component and static elimination component to the early strength component solution in batches, stir evenly, and cool to room temperature to obtain the activator.
Citation Information
Patent Citations
Slag cement exciting agent and preparation method thereof
CN113135678A
Reinforced cement grinding aid and preparation method thereof
CN103274632A
Cement regeneration technique by activating discarded concrete
CN1990410A